Parasitomimetics: Can We Utilize Parasite-Derived Immunomodulatory Molecules for Interventions to Immunological Disorders? - Nagai, Kazuki; Goto, Yasuyuki (Frontiers in Immunology, 2022)
Because our immune system has ability to expel microorganisms invading our body, parasites need evolution to maintain their symbiosis with the hosts. One such strategy of the parasites is to manipulate host immunity by producing immunomodulatory molecules and the ability of parasites to regulate host immunity has long been a target of research. Parasites can not only manipulate host immune response specific to them, but also influence the host’s entire immune system. Such ability of the parasites may sometimes bring benefit to the hosts as many studies have indicated the “hygiene hypothesis” that a decreased opportunity of parasitic infections is associated with an increased incidence of allergy and autoimmune diseases. In other words, elucidating the mechanisms of parasites to regulate host immunity could be applied not only to resolution of parasitic infections but also to treatment of non-parasitic immunological disorders. In this review, we show how much progress has been made in the research on immunomodulation of host immunity by parasites. Here, we define the word ‘parasitomimetics’ as emulation of parasites’ immunomodulatory systems to solve immunological problems in humans and discuss potential applications of parasite-derived molecules to other diseases.